2017
DOI: 10.1021/acsnano.6b08392
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Energy Transfer in Photosensitive Nanocrystal Device

Abstract: Förster resonance energy transfer (FRET) interacted with localized surface plasmon (LSP) gives us the ability to overcome inadequate transfer of energy between donor and acceptor nanocrystals (NCs). In this paper, we show LSP-enhanced FRET in colloidal photosensors of NCs in operation, resulting in substantially enhanced photosensitivity. The proposed photosensitive device is a layered self-assembled colloidal platform consisting of separated monolayers of the donor and the acceptor colloidal NCs with an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…These competitive effects are controlled by several experimental parameters, such as the spectral overlap between absorption/emission of the fluorophores and the extinction of metal nanostructures, the distance between the metal surface and the fluorophores, and the absorption/scattering ratio of the nanostructures . In plasmon‐modulated FRET, the interactions between different entities are even more complicated . Single‐particle experiments have suggested that the FRET channel is turned on when the LSPR of plasmonic nanocrystal lies between the emission peak of the donor and absorption peak of the acceptor or right at the emission wavelength of the acceptor, and is turned off, while the LSPR is at the emission wavelength of the donor .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These competitive effects are controlled by several experimental parameters, such as the spectral overlap between absorption/emission of the fluorophores and the extinction of metal nanostructures, the distance between the metal surface and the fluorophores, and the absorption/scattering ratio of the nanostructures . In plasmon‐modulated FRET, the interactions between different entities are even more complicated . Single‐particle experiments have suggested that the FRET channel is turned on when the LSPR of plasmonic nanocrystal lies between the emission peak of the donor and absorption peak of the acceptor or right at the emission wavelength of the acceptor, and is turned off, while the LSPR is at the emission wavelength of the donor .…”
mentioning
confidence: 99%
“…Despite these advantages incurred by plasmon modulation, there is still no planar plasmonic substrate available to serve as a universal platform for tailored on‐surface FRET enhancement, which is highly desirable for biosensing, optical imaging, and solar energy conversion applications. 2D substrates, such as electrostatically adsorbed metal nanoparticle monolayers and plasmonic gratings have been used to study plasmon‐controlled FRET at a fundamental level. However, these plasmonic substrates, along with other possible choices, such as gold‐island films, show at least three interconnected problems in practical applications.…”
mentioning
confidence: 99%
See 3 more Smart Citations